Disponibilidad de leche de los países sudamericanos en las últimas cinco décadas : elementos para análisis y perspectivas futuras (2019)
ABSTRACT: The aim of this study was to compare the per capita milk supply between South American countries during the last five decades. The data in the food balance sheets reported by the FAO were analyzed through a general lineal model with Tukey contrast as well as one-dimensional exploratory descriptive statistics, Cluster and Biplot analyses. The South American countries exhibited differences on the quantity of milk supply for human consumption. Uruguay and Argentina showed the greater milk supply throughout the period while Bolivia, Peru and Paraguay the lower. There is a gap between the quantity of milk supply and the nutritional needs of the foodstuff. Despite the majority of the South American countries increased the quantity of milk along time, none of them achieved the international nutritional recommendation.